THU0373 The markers useful in predicting lupus nephritisin clinical practice. (12th June 2018) - Dabrowski, P.; Marczak, K.; Gala-Bladzińska, A.; Gargasz, K.; Dabrowska, M.
Abstract : Background: Lupus nephritis (LN) is one of the most severe clinical manifestations of systemic lupus erythematosus (SLE). LN can be found in approximately 50% of SLE patients. The renal biopsy remains the gold diagnostic standard. However non-invasive and clinically practical laboratory markers of kidney damage in this disease are sought. Objectives: The aim of the study was to assess the utility of biomarkers like inflammable indicators, complement system components and albuminuria in a single urine sample for prediction of kidney involvement and disease activity in patients with SLE. Methods: A prospective study included 33 patients (81.8% women) with SLE criteria according to SLICC (Systemic Lupus International Collaborating Clinics) in age of 39.0±14.3 years. Disease-duration ranged 6–60 months. We performed full physician examination and we excluded patients with active infection. The disease activity based on the SELENA-SLEDAI scale was assessed and divided into groups: low activity (L)<6, moderate (M) 7–12, high (H)>12 points. In the blood samples complement components (C3, C4) (g/L), C-reactive protein CRP (mg/L), interleukin 6 (IL-6) (pg/mL), serum creatinine concentration (sCr) (mg/g), ESR (mm/h), glomerulal filtration rate (eGFR) according to CKD-EPI (ml/min/1.73 m 2 ) were determined. The concentration of albumin (uAlb) (mg/dl) and creatinine sCr (g/dL) from the morning urine sample was measured and the albumin/creatinine index (uACR) (mg/g) was calculated. Based on the obtained results, patients were divided into stages of chronic kidney disease (CKD) according to .KDIGO 2012. A daily proteinuria (DP) (g/24 hour) was performed. In the assessment of statistical significance, Kruskal-Wallis or Mann-Whitney U-tests were used. Results: In our study the SLE activity was as follows (%): L-24 (72.7), M-6 (18.2), H-3 (9.1). The average values (range) of biomarkers of renal function were: Cr=0, 81±0, 27 (0.55–1.65), eGFR=99.6±24.4 (46–131), uAlb=13.6±34.4 (0.04–161.0), uACR=121.3±356.3 (4.8–1905.3), DP=0.32±0.92 (0.015–5.3), and other biomarkers: OB=26.1±25.9 (4.0–99.0); CRP=10.3±28.1 (0.2–148.7); IL-6=7.8±14.7 (0–78.3); C3=1.08±0.36 (0.33–2.25); C4=0.16±0.09 (0.02–0.43). The study group met the CKD criteria: G1 n=21 (63.6%), G2 n=9 (27.3%), G3 n=3 (9.1%); A1 n=26 (78.8%), A2 n=3 (9.1%), A3 n=4 (12.1%). We showed a negative relationship between the eGFR and: CRP (R=-0.49, p=0.005), IL-6 (R=-0.48, p=0.005) and C4 (R=-0.43, p=0.01). There was also a significant dependence of the SLEDAI SLE activity with: uAlb (L, H) (p=0.04), DP (M, H) (p=0.03), uACR in the whole study group (p=0.04) and between uACR and DP (p=0.0003). Conclusions: Our studies showed that the risk of kidney damage in SLE may depend on the concentration of CRP, IL-6, C4. In addition albuminuria (uAlb, uACR) correlates with the value of DP and SLE activity, what indicates the dominant glomerular lesion in the etiopathogenesis of proteinuria in LN. Disclosure of Interest: None declared